Restoring Treatment Response in Colorectal Cancer Cells by Targeting MACC1-Dependent ABCB1 Expression in Combination Therapy - Dahlmann, Mathias; Werner, Rebecca; Kortüm, Benedikt; Kobelt, Dennis; Walther, Wolfgang; Stein, Ulrike (Frontiers in Oncology, 2020)
Treatment failure of solid cancers, represented by the development of drug resistance in the primary tumor or later outgrowth of drug resistant metastases, is the major cause of death for cancer patients. It represents an urgent clinical need for predictive biomarkers which indicate the success or failure of standard treatment regimens. Besides treatment prediction, interfering with cellular processes associated with drug resistance might improve treatment response by applying combination therapies. Metastasis-Associated in Colon Cancer (MACC) 1 was identified in our group as a prognostic biomarker in human colorectal cancer, and has been established as key player, prognostic and predictive biomarker for tumor progression and metastasis in a variety of solid cancers. Besides increased cell proliferation and motility, subsequently contributing to growth and metastatic spread of the primary tumor, MACC1 has also been shown to dysregulate apoptosis and is contributing to treatment resistance. Here we report the MACC1 dependent treatment resistance of colorectal cancer (CRC) cells to standard therapeutics like doxorubicin by upregulating ATP-cassette binding (ABC) B1 protein (also referred to as p-glycoprotein (Pgp) 1 and multi-drug resistance protein (MDR) 1). Overexpression of MACC1 in CRC cells increased ABCB1 expression and thus treatment resistance to standard therapeutics, whereas depleting MACC1 increased intracellular drug concentrations, leading to better treatment response. We already identified the first MACC1 transcriptional inhibitors, such as lovastatin, by high-throughput screening of clinically approved small molecule drugs. These compounds inhibited cell motility in vitro but also restricted metastasis development in xenograft mouse models by reducing MACC1 expression. Here we report, that treating high MACC1 expressing CRC cells with a combination of statins and standard therapeutics increased the rate of cytotoxicity and resulted in higher treatment response.